Clinical overview of the physiology and pathophysiology of pleural fluid movement: a narrative review - Lucía Ferreiro; María E. Toubes; Juan Suárez-Antelo; Nuria Rodríguez-Núñez; Luis Valdés (ERJ Open Research, 2024)
In physiological conditions, the pleural space couples the lung with the chest wall and contains a small amount of fluid in continuous turnover. The volume of pleural fluid is the result from the balance between the entry of fluid through the pleural capillaries and drainage by the lymphatics in the most dependent areas of the parietal pleura. Fluid filtration is governed by Starling forces, determined by the hydrostatic and oncotic pressures of the capillaries and the pleural space. The reabsorption rate is 28 times greater than the rate of pleural fluid production. The mesothelial layer of the inner lining of the pleural space is metabolically active and also plays a role in the production and reabsorption of pleural fluid. Pleural effusion occurs when the balance between the amount of fluid that enters the pleural space and the amount that is reabsorbed is disrupted. Alterations in hydrostatic or oncotic pressure produce a transudate, but they do not cause any structural damage to the pleura. In contrast, disturbances in fluid flow (increased filtration or decreased reabsorption) produce an exudate via several mechanisms that cause damage to pleural layers. Thus, cellular processes and the inflammatory and immune reactions they induce determine the composition of pleural fluid. Understanding the underlying pathophysiological processes of pleural effusion, especially cellular processes, can be useful in establishing its aetiology.